Serotype distribution of dengue virus in Trang Province, Southern Thailand, 2024 - Sapcharoen, Suwandee; Sawetadul, Ativet; Panich, Tipattaraporn; Nigapruke, Khatayut (Journal of Associated Medical Sciences, 2025)
Background: Dengue fever is a significant public health concern in Thailand, which consists of Aedes mosquitoes as a vector. The incidence of dengue fever has increased, positioning it among the top 10 infectious diseases affecting health in the Southern region of Thailand. Objectives: This study aimed to examine serotypes and genotypes of the dengue virus causing dengue fever in Trang province in 2024. Materials and methods: From April to August 2024, a total of 125 acute serum or plasma samples were collected from patients with dengue NS1 antigen screening test positive results and/or were clinically diagnosed with dengue fever. The samples were tested for dengue viral RNA detection and serotyping using real-time RT-PCR. Genotype identification was performed using whole-genome sequencing. Results: Of these, 73 samples (58.4%) were detected for dengue viral RNA. The predominant serotype was DENV-3 (N=31, 42.5%), followed by DENV-2 (N=27, 37.0%), DENV-4 (N=13, 17.8%), and DENV-1 (N=2, 2.7%). By analyzing and comparing the whole genome sequence of 3 samples (TR-22, TR-37, and TR-38), all results were DENV-4 Genotype I. The percent of identity for genotype classification ranged from 95.1% to 99.3%. Conclusion: The findings would be useful for establishing effective control and prevention measures for the outbreaks and could contribute to the development of diagnostic tests and vaccines in the future.